Korelasi antara Tipe Kepribadian dan Tingkat Burnout pada Mahasiswa Kedokteran Universitas Negeri di Jakarta Selatan - Alvina, Alvina; Zalfa Kaila Pramariza (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2026)
Introduction: Medical students are at high risk of burnout due to academic demands and psychological stress during their studies. Burnout can impact mental health, academic performance, and professional preparedness. Personality types are considered potential factors influencing vulnerability to burnout. Purpose: To examine the relationship between personality type and burnout levels among medical students. Methods: A quantitative cross-sectional study was conducted involving 136 medical students. Personality types were assessed using the Big Five Inventory-2 Short Form (BFI-2-S), while burnout was measured with the Maslach Burnout Inventory-Student Survey (MBI-SS). Data were analyzed using Spearman correlation test. Results: Most respondents were categorized as moderate across all personality dimensions, and 86.8% experienced high burnout. Significant correlations were found between all personality dimensions and burnout. Neuroticism showed a positive correlation (r = 0.357; p < 0.001), whereas extraversion (r = -0.295; p < 0.001), agreeableness (r = -0.259; p = 0.002), conscientiousness (r = -0.339; p < 0.001), and openness (r = -0,304; p < 0.001) showed negative correlations. Conclusion: Big Five personality types are associated with burnout among medical students. Neuroticism relates to higher burnout levels, while other dimensions are associated with lower burnout levels.